Most important barriers and facilitators of HTA usage in decision-making in Europe. (4th May 2018) - Cheung, K.L.; Evers, S.M.A.A.; De Vries, H.; Levy, P.; Pokhrel, S.; Jones, T.; Danner, M.; Wentlandt, J.; Knufinke, L.; Mayer, S.; Hiligsmann, M.
ABSTRACT: Background : To enhance usage of health technology assessment (HTA) in decision-making, it is important to prioritise important barriers and facilitators to the uptake of HTA. This study aims to quantify and compare the relative importance of barriers and facilitators regarding the use of HTA in several European countries. Methods : A survey containing two best-worst scaling (BWS) object case studies (i.e. barriers and facilitators) were conducted among 136 policy makers and HTA researchers from the Netherlands, Germany, France, and United Kingdom. Hierarchical Bayes analysis generated the mean relative importance score (RIS) for each factor and subgroup analyses assessed differences between countries. Results : Six barriers (RIS≥5) and five facilitators (RIS≥6) were deemed highly important. Eleven barriers and ten facilitators differed in their importance between countries. Policy characteristics, research & researcher characteristics, and organisation & resources were particularly important to facilitate uptake of HTA, such as an explicit framework for decision-making and research of sufficient quality. Conclusion : The most paramount barriers and facilitators to HTA usage were quantified. For all countries it is crucial to create an explicit framework for the decision-making context to include HTA evidence. Country differences in the quality of research emphasize the need for enhanced international collaboration in HTA.